2012
DOI: 10.1039/c2ce25589h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structures, and properties of alkali and alkaline earth coordination polymers based on V-shaped ligand

Abstract: A series of metal coordination polymers, [Li 2 (OBA)] (1), [Na 2 (OBA) 7), and [Sr(OBA)(H 2 O)] (8) (H 2 OBA = 4,49-oxybisbenzoic acid), was synthesized from alkali and alkaline-earth metal salts and 4,49-oxybisbenzoic acid by solvothermal reactions. Single crystal X-ray structure analysis revealed that compounds 1-5 and 7-8 are three-dimensional while complex 6 has a layered structure. The inorganic motifs, ranging from discrete octahedra (6), edge-sharing octahedral dimers ( 7), and straight one-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 98 publications
2
9
0
Order By: Relevance
“…The TGA and PXRD results revealed that the complex can retain its original framework structure up to 350 ∘ C. It is also to be noted that the complex exhibited promising photoluminescence properties. The observed results are very much comparable with our previous report [40].…”
Section: Resultssupporting
confidence: 93%
“…The TGA and PXRD results revealed that the complex can retain its original framework structure up to 350 ∘ C. It is also to be noted that the complex exhibited promising photoluminescence properties. The observed results are very much comparable with our previous report [40].…”
Section: Resultssupporting
confidence: 93%
“…During the first cycle, the rapid decrease in charge/ discharge capacities of complex 3 and complex 4 might be due to the irreversible electrochemical nature of the lithium complexes, which is quite common for lithium-containing compounds. These results reveal that both lithium coordination polymers have active electrochemical properties and display similar capacity, in comparison to previously reported studies where they ranged from about 100 to 600 mAhg −1 [33,34,35,36,37,38,39,40,41,42,43,44].…”
Section: Resultssupporting
confidence: 63%
“…There have been few studies on lithium CPs with interesting electrochemical behaviors that could be used as electrodes in lithium ion batteries [33,34,35,36,37,38,39,40,41,42,43,44]. For the first time, two CPs of lithium terephthalate (Li 2 C 8 H 4 O 4 ) and lithium trans – trans –muconate (Li 2 C 6 H 4 O 4 ) displayed high electrode capacities up to 300 mAhg −1 [34].…”
Section: Introductionmentioning
confidence: 99%
“…10 Since then, Li + -based MOFs have been reported using linkers as varied as amino acids, thiophenedicarboxylates, and anthraquinones. [11][12][13][14][15][16] These Li + -based MOFs have been shown to display properties such as luminescence, [17][18][19] gas uptake, [20][21] and even have potential applications as electrodes in Li batteries. 13 Some Na + -based MOFs have also been reported to possess similar properties to their Li + analogs such as gas sorption, luminescence, and anodes for Na batteries.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] These Li + -based MOFs have been shown to display properties such as luminescence, [17][18][19] gas uptake, [20][21] and even have potential applications as electrodes in Li batteries. 13 Some Na + -based MOFs have also been reported to possess similar properties to their Li + analogs such as gas sorption, luminescence, and anodes for Na batteries. [22][23][24] Despite this, Na + -based MOFs have been less well studied, partly because the larger cation size results in increased coordination to polar solvents which favors low dimensional coordination networks.…”
Section: Introductionmentioning
confidence: 99%